2015
DOI: 10.3892/ijo.2015.3287
|View full text |Cite
|
Sign up to set email alerts
|

PIK3R1 targeting by miR-21 suppresses tumor cell migration and invasion by reducing PI3K/AKT signaling and reversing EMT, and predicts clinical outcome of breast cancer

Abstract: We have previously shown that dysregulation of miR-21 functioned as an oncomiR in breast cancer. The aim of the present study was to elucidate the mechanisms by which miR-21 regulate breast tumor migration and invasion. We applied pathway analysis on genome microarray data and target-predicting algorithms for miR-21 target screening, and used luciferase reporting assay to confirm the direct target. Thereafter, we investigated the function of the target gene phosphoinositide-3-kinase, regulatory subunit 1 (α) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 47 publications
4
65
1
1
Order By: Relevance
“…Phosphoinositide-3-kinase regulatory subunit 1(PIK3R1) binds, stabilizes and inhibits the PI3K p110 catalytic subunit [39]. Previous studies show that PIK3R1 suppresses tumor cell invasion and migration by reducing PI3K/AKT signaling [40]. In this study, ITGB1, HIF1A, and PIK3R1 were selected as core mRNAs with important function in advanced LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoinositide-3-kinase regulatory subunit 1(PIK3R1) binds, stabilizes and inhibits the PI3K p110 catalytic subunit [39]. Previous studies show that PIK3R1 suppresses tumor cell invasion and migration by reducing PI3K/AKT signaling [40]. In this study, ITGB1, HIF1A, and PIK3R1 were selected as core mRNAs with important function in advanced LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that miR-21 positively regulates the PI3K/Akt signaling pathway (18,36,37). miR-21 suppresses tumor cell migration and invasion by reducing PI3K/Akt signaling and reversing the epithelial-mesenchymal transition in breast cancer (36). miR-21 also modulates the radiosensitivity of cervical cancer by inhibiting autophagy via the Akt-mTOR signaling pathway (37).…”
Section: Discussionmentioning
confidence: 99%
“…The current results further proved the role of CDK1 in NSCLC, and CDK1 was the key gene in the PPI network. At present, PIK3R1 has been proved to be a double-sided factor in different cancers, and was a positive regulator in breast and endometrial cancers (41,42) and was a negative regu-…”
Section: Discussionmentioning
confidence: 99%